Biocompatibility of acetazolamide pastes in the subcutaneous tissue of rats - Mori, Graziela Garrido [UNESP]; de Moraes, Ivaldo Gomes; Nunes, Daniele Clapes [UNESP]; Castilho, Lithiene Ribeiro [UNESP]; Poi, Wilson Roberto [UNESP] (FapUNIFESP (SciELO), 2009)
This aim of this study was to investigate the biocompatibility of two experimental acetazolamide (AZ)-based pastes in the subcutaneous tissue of rats. Both pastes contained AZ as the main component in similar concentration. The vehicle in experimental paste 1 was saline, while experimental paste 2 was prepared with propylene glycol. Sixty polyethylene tubes were sealed at one end with gutta-percha (GP), which served as a control. Half of the tubes were flled with paste 1 and half with paste 2. The tubes were implanted in the subcutaneous tissue of 15 rats, being 4 tubes for each animal. The animals were killed 7, 15 and 45 days after surgery and the specimens were processed in laboratory. The histological sections were stained with hematoxylin and eosin and were analyzed by light microscopy. Scores were assigned to level of infammatory process: 1- none; 2- mild; 3- moderate; 4- severe. The data were analyzed statistically by the Kruskal-Wallis test (p≤0.05). Paste 1 produced an infammatory process at 7 days. However, the intensity of this infammation decreased with time and was nearly absent at 45 days. No statistically signifcant difference (p>0.05) was observed between the control (GP) and paste 1. However, paste 2 produced infammatory response at all study periods and differed signifcantly (p<0.05) from the control. In conclusion, in the present study, the experimental AZ-based paste 1 was considered as biocompatible as the control matrial (GP), while experimental paste 2 was irritating to rat subcutaneous tissue.
Keywords: Acetazolamide; Biocompatibility; Rat; acetazolamide; biomedical and dental materials; drug carrier; propylene glycol; sodium chloride; animal; drug effect; endodontics; male; rat; subcutaneous tissue; tooth disease; tooth injury; Wistar rat; Animals; Drug Carriers; Male; Propylene Glycol; Rats; Rats, Wistar; Root Canal Irrigants; Root Resorption; Sodium Chloride; Subcutaneous Tissue; Tooth Avulsion; Tooth Replantation